31=6+9(k+7)

Simple and best practice solution for 31=6+9(k+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 31=6+9(k+7) equation:


Simplifying
31 = 6 + 9(k + 7)

Reorder the terms:
31 = 6 + 9(7 + k)
31 = 6 + (7 * 9 + k * 9)
31 = 6 + (63 + 9k)

Combine like terms: 6 + 63 = 69
31 = 69 + 9k

Solving
31 = 69 + 9k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-9k' to each side of the equation.
31 + -9k = 69 + 9k + -9k

Combine like terms: 9k + -9k = 0
31 + -9k = 69 + 0
31 + -9k = 69

Add '-31' to each side of the equation.
31 + -31 + -9k = 69 + -31

Combine like terms: 31 + -31 = 0
0 + -9k = 69 + -31
-9k = 69 + -31

Combine like terms: 69 + -31 = 38
-9k = 38

Divide each side by '-9'.
k = -4.222222222

Simplifying
k = -4.222222222

See similar equations:

| 2-7R=-75 | | 65-92= | | -12=12y | | 4/x+6=8/3x+5 | | 6x^2+7x-25=0 | | -(1-6b)=-3+2(2b-4) | | 3h-7=-2 | | 90=(3x-5)+(2x) | | 6x^2+7x-21=0 | | y=-5/7x-4 | | 123+180=180 | | -2ab-ab= | | (-92)+63= | | 5g+9=5 | | 5(c-2)=5b-3 | | 6-4=7X-9X-8 | | 5g+9=-5 | | -2r=-34 | | 1.2(x-5)=1.6(2x+5) | | (x+3)(x+3)=12*x | | (2m+3)(6m-2)= | | 10x+-9x= | | 3r^2-9r-17=2r^2-5-8r | | 44x+7=73 | | 123+45=180 | | -2(8+4h)= | | x=5.6+1.4y | | 123+70=180 | | 2g+5=-3 | | (-7n/12)(9n/14) | | 9-5x=6x | | (2y-3)/(y+3)=5/7 |

Equations solver categories